Integration Sistem Dalam Meningkatkan Efisiensi Dan Inventivitas Pertanian Berkelanjutan - Mendrofa, Marta Tristanti; Wahyuni (CV. SINAR HOWUHOWU, 2025)
Sustainable agriculture plays a key role in addressing global food security challenges. In this case, the application of technology is very important to increase efficiency and productivity in the agricultural sector. The aim of this research is to explore the application of various solutions, such as sensor-based monitoring systems, mobile applications for land management, and agricultural data analysis that can help farmers make more informed decisions. Research findings show that the use of technology not only contributes to increasing crop yields, but also optimizes the use of resources such as water and fertilizer, thereby encouraging more environmentally friendly agricultural practices. Thus, integration in sustainable agriculture can be an effective approach in achieving food security and sustainability goals.